2020
DOI: 10.1016/j.jamda.2020.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Age, Frailty, and Comorbidity as Prognostic Factors for Short-Term Outcomes in Patients With Coronavirus Disease 2019 in Geriatric Care

Abstract: Objectives To analyze whether frailty and comorbidities are associated with in-hospital mortality and discharge to home in older adults hospitalized for coronavirus disease 2019 (COVID-19). Design Single-center observational study. Setting and Participants Patients admitted to geriatric care in a large hospital in Sweden between March 1 and June 11, 2020; 250 were treated for COVID-19 and 717 for other diagnoses. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
188
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(213 citation statements)
references
References 21 publications
18
188
3
4
Order By: Relevance
“…For the same reason, we could not collect any frailty scale data in this study. Recently, it has been reported that the level of frailty is a useful predictor of short-term COVID-19 outcomes in geriatric patients ( 45 ). However, a fair relationship between frailty and the Barthel Index in hospitalized older patients has been demonstrated ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the same reason, we could not collect any frailty scale data in this study. Recently, it has been reported that the level of frailty is a useful predictor of short-term COVID-19 outcomes in geriatric patients ( 45 ). However, a fair relationship between frailty and the Barthel Index in hospitalized older patients has been demonstrated ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our data confirmed that deceased patients showed an overall higher Charlson comorbidity index, but dementia and renal disease were significantly higher. Indeed, COVID‐19 patients with cognitive impairment are at high risk of worse outcome, and this is a major challenge in geriatric populations 6,23,24 …”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the resolution of inflammation is impaired with ageing ( Arnardottir et al, 2014 ), which may explain why younger people are less affected in COVID-19. In addition to age, the level of frailty is a predictor of short-term COVID-19 outcomes in older patient populations ( Hägg et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%